Tonal noise measurements of a small propeller in an open and closed test facility - Bokhorst, E. van; Brouwer, H.H. (AIAA, 2022)
In this paper experiments and simulations on tonal noise of a small propeller are described. Experiments were carried out in the open-jet and closed test section configuration of the Aeroacoustic Wind Tunnel at NLR Marknesse. From previous investigations it has been found that when acoustic beamforming techniques are applied, the acoustic source is not located at the propeller blade itself. Therefore a new propeller steering function for acoustic beamforming is introduced which incorporates the operating conditions of the propeller. With the new steering function it is more easy to identify the source location however the large depth of field prevents the possibility to use three dimensional beamforming. Instead, to define the y-coordinate of the virtual source location the openjet simulations are used. The final comparison between the open-jet and closed test section measurements shows that the resonances in the tunnel and reflections influence the sound pressure levels significantly. More work is needed to fully understand these effects.